The Effectiveness of Cryotherapy and Dynamic Stretching on Muscle Recovery of Young Basketball Athletes After Intensive Training - Aziz, Muhamad Ivan Muftahul; Jahrir, Andi Sahrul (Universitas Negeri Jakarta, 2025)
Optimal muscle recovery is essential for basketball athletes to maintain performance and prevent injury. Cryotherapy and dynamic stretching are two popular recovery methods, but the comparative effectiveness of the two still needs further research. The purpose of this study was to determine the effectiveness of cryotherapy and dynamic stretching on reducing muscle soreness in young basketball athletes after intensive training. This research method is a quasi-experiment with a pre-test post-test design in two groups. The sample of 22 basketball athletes BKMF FIKK UNM was divided into cryotherapy (n = 11) and dynamic stretching (n = 11) groups. Muscle pain levels were measured using Visual Analogue Scale (VAS) at 30 minutes, 24 hours, and 72 hours post-test. Analysis using independent t test, and ANOVA. Results showed that both groups experienced a significant decrease in VAS scores at all measurement times (p<0.001). At 72 hours post-test, cryotherapy showed lower VAS score (3.39 ± 0.42) than dynamic stretching (3.81 ± 0.50) with significant difference (p=0.047). There was a significant effect of intervention type (p=0.000), measurement time (p=0.000), and their interaction (p=0.005). This study shows that cryotherapy and dynamic stretching are effective in reducing muscle pain, but cryotherapy is superior in the final phase of recovery.